Thermographic evaluation of piroxicam’s effect as an adjuvant treatment in canine mammary tumors (Research, Society and Development, 2021)
Mammary tumors are the second most diagnosed neoplasms in dogs. Canine females are largely affected by malignant mammary tumours. Several factors are involved in the development and determination of the malignancy of these lesions, including the action of cyclooxygenase-2. Use of non-steroidal anti-inflammatory drugs as enzyme-inhibiting drugs has been studied as a promising adjuvant treatment for neoplasms. The aim of this study was to evaluate the effect of piroxicam in reducing inflammation caused by mammary tumours in 25 bitches during 10 days of administration based on the measurement of peritumoral temperature using thermography. The results indicated a significant difference (p=0,003) between the average temperatures at the first and last day of treatment. When performing the evaluation of malignant and benign neoplasms separately, it was possible to observe that, statistically, malignant neoplasms (n=19) showed a significant reduction in peritumoral temperatures (P=